Disability and intersecting statuses - Barnartt, Sharon N.; Altman, Barbara Mandell (Bingley, U.K. : Emerald, 2013)
Disability can be either an ascribed status or an achieved status and its combination with other statuses will affect the persons social experiences. The term intersectionality has been used most often to discuss the ways in which the dual and simultaneous statuses of 'black' and ''female' exist as facets of social structure and culture, interact in both those spheres, and affect individuals in ways which neither one does separately. Little attention has been paid to disability in this context, despite the many parallels to race and gender. This volume challenges critical thinking about the interrelationships with disability. It questions if the concepts and methods of intersectionality can be applied to disability at all or if they can be applied in the same way. The authors debate whether different conception of intersectionality would fit the disability context better and if there are methodologies which could be used to examine it. A variety of empirical evidence about situations in which disability intersects with other roles are also examined.
Introduction : disability and intersecting statuses / Sharon N. Barnartt -- At the intersection of feminist and disability rights movements. From equality in difference to human diversity claims / Míriam Arenas Conejo -- Intersectionality and the disability : some conceptual and methodological challenges / Anthony Sommo, Jay Chaskes -- Unmet needs and quality of support for parents of transition-aged youth : differences by disability group, age, and household income / Lynda L. Anderson, Sheryl A. Larson, Shauna McDonald -- Has the parent experience changed over time? A meta-analysis of qualitative studies of parents of children with disabilities from 1960 to 2012 / Sara E. Green, Rosalyn Benjamin Darling, Loren Wilbers -- Disability and participation : assessing employment and education outcomes in the national health interview survey (2010) / Mitchell Loeb ... [et al.] -- Aging into disability beyond 50 : the impact on labor force participation and earnings / Charles Roehrig, Douglas Klayman, Kristen Robinson -- "You're so short!" : the stigma (and disability) of being a short woman / Leslie Rott -- Wear and tear : the social production of disablement in construction workers / Amy M. Sorensen -- Social class and learning disabilities : intersectional effects on college students in New York City / Ashleigh Thompson -- Disability, gender and caste intersections in Indian economy / Nilika Mehrotra.
Print version record
Keywords: Social Science / People with Disabilities; Social Science -- General; Disability: social aspects; Personal & social issues: disability & special needs (Children's/YA); People with disabilities -- Social conditions; Sociology of disability